The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1080/15548627.2022.2025571
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of autophagy in exacerbation of eosinophilic airway inflammation in a murine model of obese asthma

Abstract: Obesity is a common comorbidity in patients with asthma, and obese asthma patients present the most refractory phenotype among patients with severe asthma. Similar to the observations in non-obese asthma patients, clinical studies have revealed heterogeneity in obese asthma patients, including the occurrences of T helper (Th)2-high and Th2-low phenotypes. However, the mechanisms underlying obesity-related asthma are not completely understood. Though macroautophagy/autophagy is involved in asthma and obesity, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Previous studies have shown that it contributes to the extracellular trap formation and exacerbation of eosinophilic inflammation in asthma. 29 , 30 , 31 , 32 Heightened ER stress is associated with severe eosinophilic in asthma and lipid mediators such as LTB4, LTD4 and platelet-activating factors are potent chemoattractants for eosinophils. 33 , 34 Of interest, ROS acts as an upstream regulator of ER stress and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that it contributes to the extracellular trap formation and exacerbation of eosinophilic inflammation in asthma. 29 , 30 , 31 , 32 Heightened ER stress is associated with severe eosinophilic in asthma and lipid mediators such as LTB4, LTD4 and platelet-activating factors are potent chemoattractants for eosinophils. 33 , 34 Of interest, ROS acts as an upstream regulator of ER stress and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that autophagy contributes to the exacerbation of eosinophilic inflammation in obese asthma by the development of TSLP-and IL33dependent eosinophilic inflammation. 71 Mouse studies suggested that the nucleotidebinding domain, leucine-rich repeat-containing family, and pyrin domain-containing-3-IL1b-IL17 axis elicit the relationship between excess adiposity and non-atopic adult-onset asthma. 72,73 Obesity is associated with poorer BA control.…”
Section: Obesitymentioning
confidence: 99%
“…Besides, in ATG5-deficient mice, lack of autophagy causes neutrophilic airway inflammation and hyperreactivity, concomitant with increased IL-1 β and IL-17 levels in lung lysates upon house dust mite sensitization and challenge [ 33 ]. Likewise, enhanced eosinophilic inflammation and airway hyperreactivity are also observed in ATG5-deficient obese mice compared to wild type obese mice, suggesting that autophagy mitigates the exacerbation of eosinophilic inflammation in obese asthma [ 34 ]. Intriguingly, the level of autophagy differs in distinct cell types in asthma-like animal models.…”
Section: Autophagy and Asthmamentioning
confidence: 99%